The Optimism Scale Based on Explanatory Style: Evidence of Psychometric Validity in Indonesian High School Students - Thoriq Asshiddiqie; Rahman Pranovri Putra; Rosita Endang Kusmaryani; Farida Agus Setiawati; Auliya Ramadhanti; Barreiro Annemari (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: The purpose of this study was to provide psychometric evidence of the Optimism Scale based on Explanatory Style in high school students in Indonesia. Methodology: The type of research is quantitative research with a survey type. This study was conducted with EFA factor analysis, which was used for initial exploration in scale development and CFA, which was used to confirm a predetermined factor model based on the results of EFA., the optimism scale consisted of 32 items, and the number of subjects in this study was 186 students. The data were analysed using the Jamovi program version 2.4.11. Main Findings: The results of this study indicate that there are 3 factors after EFA, and after CFA there are 7 items that are dropped, leaving 25 items with CFA values of CFI = 0.911, TLI = 0.902, SRMR = 0.0553, RMSEA = 0.0508 and McDonald's Omega reliability of 0.872 and Cronbach's alpha of 0.872. Novelty/Originality of this study: This study offers an explanatory style-based optimism scale with comprehensive psychometric validity evidence in Indonesian high school students. This study makes a novel contribution in the development of instruments that are appropriate to the Indonesian cultural context, as well as supporting the measurement of optimism in educational settings to understand students’ positive thinking patterns in order to improve their psychological well-being and academic achievement.